Performance improvement of multipulse rectifiers using half-controlled DCM boost converters - Junior, Joao Carlos Pelicer [UNESP] (2015)
The multipulse converters are widely applied in the AC-DC conversion, once these structures take advantage of the phase-displacement provided by the transformer or autotransformer to mitigate part of the harmonic content injected in the grid. This work proposes a novel structure using a half-controlled multipulse boost-based converter, operating in Discontinuous Conduction Mode (DCM) aiming reducing the Total Harmonic Distortion (THD) of the line content. The simulation analysis shows a significant improvement of the Power Factor (PF) due to the THD being 0.88%while the conventional 12-pulse topologies, the THD is about 14%. Each conventional three-phase bridge rectifier is replaced by a three-phase half-controlled boost-based topology, also called of bridgeless rectifier. The DCM strategy is useful to eliminate the need of current sensors and achieve the high PF through the bridgeless rectifier because the peaks of the current naturally follow the grid voltage waveform. Other feature of this proposed topology refers to the robustness. All the switches are placed on the same reference. The control circuit becomes very simplified because all the switches are synchronized and only one basic voltage loop is used to regulate the DC output, without current sensors.